Oggie Cooder, party animal - Weeks, Sarah; Holgate, Douglas (New York : Scholastic Press, 2009)
Neither a long list of rules, nor the inability to find the perfect gift--Cheddar Jam--nor being locked in a bathroom with a juggling bear will keep quirky fourth-grader Oggie Cooder from attending neighbor Donnica Perfecto's birthday pool party.
U
860
U
Keywords: Eccentrics and eccentricities -- Fiction; Parties -- Fiction; Birthdays -- Fiction; Neighbors -- Fiction; Friendship -- Fiction; Schools -- Fiction